Odpowiedzi

Najlepsza Odpowiedź!
2010-03-12T22:44:53+01:00
A)
a2=6 i a10=2

a10 = a1+(10-1)r i a2 = a1+r

z drugiego równania: a1 = a2-r
czyli a1 = 6-r

2 = 6-r +9r = 6 - 8r
-8r = -4
r = 0,5

a1 = 5,5

wzór:
an = 5,5+(n-1)*0,5

b)

b3=11 i b9=35


b9 = b1+(9-1)r i b3 = b1+2r

z drugiego równania: b1 = b3-2r czyli b1 = 11+2r

b9 = 35=11+2r+8r = 11+10r

10r = 24
r = 2,4

b1= 11+ 4,8 = 15,8

wzor:
bn = 15,8 + (n-1)*2,4



18 1 18
  • Użytkownik Zadane
2010-03-12T22:45:34+01:00
A) a₂= 6 i a₁₀= 2

a₁+r=6
a₁+9r=2/*(-1)

a₁+r=6
-a₁-9r=-2
-8r=4/(-8)
r=-½

an=a₁+(n-1)*r
an=6 ½+(n-1)*(-½)
an=6 ½- ½n+½
an=7-½n

a₁=6-r
a₁=6-(-1/2)=6½

b) b₃=11 i b₉=35

b₁+2r=11/*(-4)
b₁+8r=35

-4b₁-8r=-44
b₁+8r=35

-3b₁=-9/:(-3)
b₁=3

2r=11-b₁ /:2
r=5,5-½ b₁
r=5,5-1,5=4

bn=b₁+(n-1)*r
bn=3+(n-1)*4
bn=3+4n-4
bn=4n-1
4 4 4